KURIKULUM TERPADU PENDIDIKAN AGAMA ISLAM(DI PONDOK PESANTREN AL-IMAN TEBELIAN KABUPATEN SINTANG) - Adi Subowo; Hifza Hifza; Ubabuddin (CV. ADIBA AISHA AMIRA, 2023)
The objectives of the research were : (1) to Know the concept of integrated curriculum in Al- Iman boarding school, Tebelian Kabupaten Sintang (2) to Know the Implementation of integrated curriculum Al-Iman boarding school, Tebelian Kabupaten Sintang (3) to Know the evaluation of integratedcurriculum at Al-Iman boarding school, Tebelian Kabupaten Sintang. To achieve these objectives, The researcher used field research methods (field research) that is qualitative. In data collection, the presence of the researcher is known by informant. curriculum on Islamic Religion Madrasah Aliyah level in Al- Iman boarding school, Tebelian Kabupaten Sintang include (a) The basic idea of integrated curriculum planning began from the adoption Kulliyatul Mu curriculum